La ampliación del concepto tradicional de wrongful conception en el campo de la responsabilidad médica en Colombia (2021)
This article analyzes the liability for wrongful conception in the event of breach of the duty to disclose regarding the risk of pregnancy when using an injectable contraceptive. Based on the theoretical research method, after a review of the figure in other legal systems where it has been more developed, the author shows that Colombia proposes an expansion of the scope of medical liability based on a new event that exceeds the traditional concept of wrongful conception.